Incidence of Enuresis and Encopresis Among Children with Attention Deficit Hyperactivity Disorder in a Population-Based Birth Cohort - Mellon, Michael W. (2013)
OBJECTIVE: This study reports the incidence of enuresis and encopresis among children with attention-deficit/hyperactivity disorder (AD/HD) versus those without AD/HD. METHOD: Subjects included 358 (74.5% male) children with research-identified AD/HD from a 1976-1982 population-based birth cohort (N = 5718) and 729 (75.2% male) non-AD/HD control subjects from the same birth cohort, matched by gender and age. All subjects were retrospectively followed from birth until a diagnosis of enuresis or encopresis was made or last follow-up prior to 18 years of age. The complete medical record for each subject was reviewed to obtain information on age of initial diagnosis of an elimination disorder, frequency and duration of symptoms, identification of exclusionary criteria specified by DSM-IV, with confirmation of the diagnosis by expert consensus. RESULTS: Children with AD/HD were 2.1 (95% CI, 1.3-3.4; p = 0.002) times more likely to meet DSM-IV criteria for enuresis than non-AD/HD controls; they were 1.8 (95% CI, 1.2 – 2.7; p = 0.006) times more likely to do so than non-AD/HD controls when less stringent criteria for a diagnosis of enuresis were employed. Though not significant, children with AD/HD were 1.8 (95% CI, 0.7-4.6; p = 0.23) times more likely to meet criteria for encopresis than non-AD/HD controls. The relative risk was 2.0 (95% CI, 1.0-4.1; p = 0.05) when a less stringent definition for encopresis was utilized. CONCLUSIONS: The results of this population-based study demonstrate that children with AD/HD are more likely than their peers without AD/HD to develop enuresis with a similar trend for encopresis.